Impact of experienced HIV stigma on health is mediated by internalized stigma and depression: results from the people living with HIV stigma index in Ontario - Jason M. Lo Hog Tian; James R. Watson; Francisco Ibáñez-Carrasco; Billy Tran; Janet A. Parsons; Robert G. Maunder; Kiffer G. Card; Stefan Baral; Christian Hui; Anthony R. Boni; Monisola Ajiboye; Joanne D. Lindsay; et al. (BMC, 2021)
Abstract Background Experiences of HIV stigma remain prevalent across Canada, causing significant stress and negatively affecting the health and wellbeing of people living with HIV. While studies have consistently demonstrated that stigma negatively impacts health, there has been limited research on the mechanisms behind these effects. This study aims to identify which dimensions of stigma have significant relationships with self-rated health and examine the mechanisms by which those types of stigma impact self-rated health. Methods We recruited 724 participants to complete the People Living with HIV Stigma Index in Ontario, designed by people living with HIV to measure nuanced changes in stigma and discrimination. The present study utilizes data from externally validated measures of stigma and health risks that were included in the survey. First, we conducted multiple regression analyses to examine which variables had a significant impact on self-rated health. Results from the multiple regression guided the mediation analysis. A parallel mediation model was created with enacted stigma as the antecedent, internalized stigma and depression as the mediators, and self-rated health as the outcome. Results In the multiple regression analysis, internalized stigma (coefficient = −0.20, p < 0.01) and depression (coefficient = −0.07, p < 0.01) were both significant and independent predictors of health. Mediation analyses demonstrated that the relationship between enacted stigma and self-rated health is mediated in parallel by both internalized stigma [coefficient = −0.08, se = 0.03, 95% CI (−0.14, −0.02)] and depression [coefficient = −0.16, se = 0.03, 95% CI (−0.22, −0.11)]. Conclusions We developed a mediation model to explain how HIV-related stigma negatively impacts health. We found that that enacted stigma, or experiences of prejudice or discrimination, can lead to internalized stigma, or internalization of negative thoughts regarding one's HIV status and/or increased depressive symptoms which then may lead to worse overall health. Highlighting the importance of internalized stigma and depression has the potential to shape the development of targeted intervention strategies aimed at reducing the burden of stigma and improving the health and wellbeing of people living with HIV.